Dissecting and tracking socio-spatial disadvantage in urban Australia. (April 2015) - Pawson, Hal; Herath, Shanaka
Highlights: We identify, classify and map disadvantaged places in Sydney, Melbourne and Brisbane. Spatial concentrations of disadvantage primarily in the middle and outer suburbs. Disadvantaged places classified into four socio-economically distinct types with distinctive housing markets. During 2006–2011, disadvantage epicenters migrate outwards from CBDs. During 2006–2011, disadvantaged populations subject to intensifying spatial concentration. Abstract: Despite over 20 years of uninterrupted economic growth and population expansion, distinct concentrations of poverty and disadvantage remain extant in all Australia's major conurbations. This paper systematically identifies, classifies and maps disadvantaged places in the nation's largest cities – Sydney, Melbourne and Brisbane. Our exploratory analysis indicates the presence of four distinct disadvantaged area types across the three cities. For each city we measure the ongoing intensification of spatially concentrated disadvantage and the pace at which 'disadvantage epicentres' have continued to shift outwards in the direction of the metropolitan periphery. Contributing to this process, the small fraction of disadvantaged suburbs exiting the 'disadvantaged' cohort 2006–2011 were predominantly those located closer to CBDs. 2006–2011 change over time analysis also validates the typology in highlighting that particular types of low-income suburbs have had a disproportionate propensity to acquire 'disadvantaged' status over this period.